Microscopicpolitics and Imargination in the Shareable Intimate Rituals in the CPP_Implicações Project - Duenha, Milene Lopes (Revista Brasileira de Estudos da Presença, 2021)
How to survive the end of a world model? We could say: by opening up space so other worlds may be established, and by holding up the sky through the invention of a dance that is possible for the body that there is. In a pandemic and necropolitical context, we collectively perform and invent our rituals through video conferencing platforms in bordering actions from the project named Body, performance and the political in implication (CPP_Implications). In an artistic investigation influenced by authors such as Airton Krenan, Davi Kopenawa, Erin Manning, Baruch Spinoza, Jane Bennet and Eduardo Viveiros de Castro we cartographically coined two terms: microscopicpolitics and the act of imargination.